A novel de novo mutation in the serine-threonine kinase STK11 gene in a Korean patient with Peutz-Jeghers syndrome - Ki Chang-Seok; Sun Young-Kyu; Kang Jung-Gu; Choi Yoon-Jung; Yoo Jee-Hyoung; Yoo Jong-Ha; Lee Kyung-A; Choi Jong-Rak (BMC, 2008)
Abstract Background Peutz-Jeghers syndrome (PJS) is an unusual autosomal dominant disorder characterized by mucocutaneous pigmentation and multiple gastrointestinal hamartomatous polyps. Patients with PJS are at an increased risk of developing multi-organ cancer, most frequently those involving the gastrointestinal tract. Germline mutation of the STK11 gene, which encodes a serine-threonine kinase, is responsible for PJS. Methods Using DNA samples obtained from the patient and his family members, we sequenced nine exons and flanking intron regions of the STK11 gene using polymerase chain reaction (PCR) and direct sequencing. Results Sequencing of the STK11 gene in the proband of the family revealed a novel 1-base pair deletion of guanine (G) in exon 6 (c.826delG; Gly276AlafsX11). This mutation resulted in a premature termination at codon 286, predicting a partial loss of the kinase domain and complete loss of the C-terminal domain. We did not observe this mutation in both parents of the PJS patient. Therefore, it is considered a novel de novo mutation. Conclusion The results presented herein enlarge the spectrum of mutations of the STK11 gene by identifying a novel de novo mutation in a PJS patient and further support the hypothesis that STK11 mutations are disease-causing mutations for PJS with or without a positive family history.